125k views
3 votes
Picture to the problem sented

User Jcw
by
4.6k points

1 Answer

1 vote

Answer:

Explanation:

For the matrix equation


2X+A=B

We first subtract A from both sides to get


2X=B-A_{}

Now,


B-A=\begin{bmatrix}{-7} & {-8} & {} \\ {-2} & {6} & {} \\ {4} & {4} & {}\end{bmatrix}-\begin{bmatrix}{-3} & {0} & {} \\ {0} & {3} & {} \\ {-6} & {6} & {}\end{bmatrix}
B-A=\begin{bmatrix}{-7--3} & {-8-0} & {\square} \\ {-2-0} & {6-3} & {\square} \\ {4--6} & {4-6} & {\square}\end{bmatrix}
B-A=\begin{bmatrix}{-10} & {-8} & {} \\ {-2} & {-3} & {} \\ {10} & {-2} & {}\end{bmatrix}

Hence, we have


2X=\begin{bmatrix}{-10} & {-8} & {} \\ {-2} & {-3} & {} \\ {10} & {-2} & {}\end{bmatrix}

Dividing both sides by 2 gives


\begin{gathered} X=(1)/(2)\cdot\begin{bmatrix}{-10} & {-8} & {} \\ {-2} & {-3} & {} \\ {10} & {-2} & {}\end{bmatrix} \\ \end{gathered}
X=\begin{bmatrix}{-5} & {-4} & {} \\ {-1} & {-(3)/(2)} & {} \\ {5} & {-1} & {}\end{bmatrix}

which is our answer!

User Timocov
by
5.3k points